2019
DOI: 10.1097/pq9.0000000000000170
|View full text |Cite
|
Sign up to set email alerts
|

Improving Thermal Support in Very and Extremely Low Birth Weight Infants during Interfacility Transport

Abstract: Introduction: Review of very low birth weight (VLBW) and extremely low birth weight (ELBW) neonates transported by our specialized pediatric/neonatal transport team revealed hypothermia in up to 52% of admissions. This project aimed to decrease the incidence of hypothermia in VLBW and ELBW neonates requiring transport between facilities from 52% to <20% over 1 year. Methods: In response to gaps in knowledge and barriers to care revealed by a survey administered to trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
(28 reference statements)
1
9
0
Order By: Relevance
“… 27 Similarly, in high-income countries, a population-based cohort study in USA showed a more than 10 times higher risk of mortality in VLBW infants compared to normal weight, whereas in babies born weighing between 1500 and 2000 g, mortality was 4 times higher. 28 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 27 Similarly, in high-income countries, a population-based cohort study in USA showed a more than 10 times higher risk of mortality in VLBW infants compared to normal weight, whereas in babies born weighing between 1500 and 2000 g, mortality was 4 times higher. 28 …”
Section: Discussionmentioning
confidence: 99%
“…In the HEAT trial at the Leiden University Medical Center, in Holland, infants with hypothermia at birth and at the time of admission also continued to be hypothermic longer than those without hypothermia. 28 …”
Section: Discussionmentioning
confidence: 99%
“…Transport distance might vary in the actual situation depending on the locations of the delivery room or operating room across NICUs, for example, some could be on different floors of the same building, others could be even in different buildings. To solve this problem, we introduced an insulated pre-heated portable incubator for transportation in June 2019 [ 20 , 21 ], adding the pre-transport preheating process in the delivery room or operating room in a bundle.…”
Section: Methodsmentioning
confidence: 99%
“…These results are particularly important for neonates, especially premature ones, because expertly trained paediatric transport teams keep them warmer, less hypotensive and less acidotic. This improves their clinical evolution 5 …”
Section: General N= 1 321 Paediatric N = 754 Neonatal N = 567 Pmentioning
confidence: 91%
“…This improves their clinical evolution. 5 We concluded that the specialist paediatric transport team provided appropriate respiratory and haemodynamic support to stabilise critically ill children. More than 50% required intensive care, but the complication rate was low.…”
Section: Specialist Paediatric Transport Team Provided Appropriate Re...mentioning
confidence: 94%